Intractable Tube Ovarian Abscess : A Comprehensive Review - Marysheela David, Mini Rani Mary Beth, Ola Mousa, Sheeba Kumari, Porkodi Arjunan, Ghadeer Aqeel Alghafli, Israa Aqeel Alghafli, Aml Sayed Ali Abdelrahem (South Eastern European Journal of Public Health, 2025)
Background: Tube ovarian abscess (TOA) represents a multifaceted infectious entity involving the adnexa, typically arising as a consequence of Pelvic Inflammatory Disease (PID). In this review, the etiology, pathology, management, complications and treatment aspects are discussed. Methods: PubMed/Medline and Google Scholar databases were searched to identify studies published from 1983 to 2024 covering the etiology, pathology, management, complications and treatment aspects of TOA. Results: The review findings show that the management of TOAs still poses a significant challenge and there is still a significant danger associated with TOAs. Conclusion: The need for continuous research and the modification of treatment regimens in order to address the ever-changing problems posed by microorganisms.